Hp1bp3 loss links chromatin reorganization to metabolic vulnerability in glioma - Brittney Lozzi; Taylor A. Gatesman; Pushan Dasgupta; Debosmita Sardar; Yeunjung Ko; Chenyu Mao; Hsiao-Chi Chen; Rachel N. Curry; Dongjoo Choi; Carrie A. Mohila; Melissa L. Bondy; Ganesh Rao; et al. (Proceedings of the National Academy of Sciences, 2026)
High-grade gliomas (HGGs) are aggressive brain tumors with poor prognosis, driven in part by metabolic and epigenetic adaptations. Methionine metabolism supports HGG growth by supplying S-adenosylmethionine for methylation reactions, yet how nutrient availability influences chromatin organization in HGG remains incompletely understood. Using an immunocompetent mouse model of HGG, we found that dietary methionine restriction reduced tumor proliferation, extended survival, and induced partial nuclear inversion. We identified Hp1bp3 as a key regulator of tumor growth that functions by interacting with nuclear tethering proteins to mediate chromatin reorganization. Loss of Hp1bp3 results in the upregulation of histone demethylases leading to selective depletion of H3K9me3-marked heterochromatin and accelerated glioma growth. Combining methionine restriction with Hp1bp3 loss increased the frequency of partial nuclear inversion and further suppressed tumor progression. These findings identify Hp1bp3 as a chromatin regulator linking methionine metabolism to heterochromatin stability and suggest that dietary methionine modulation can influence the structural organization of chromatin to slow tumor growth in HGG.